Ecological restoration of small water courses, experiences from Germany and from projects in Beijing - Walter Binder; Albert Göttle; Duan Shuhuai (International Soil and Water Conservation Research, 2015)
From 2009 until 2012 the project “Watershed Management of Forest Land in Beijing, Restoration of Small Water Bodies (SWBR)” was implemented, combining Close to Nature Forest Management and Restoration of Small Water Bodies. The targets were to improve flood control, to enhance the ecological conditions by copying nature and to support the recreational value of small water bodies, all in cooperation with people living there. The efficiency of each project was proofed by comparison of biological and hydro-morphological assessment before the projects started and 2–3 years after they were finished. The results confirmed the ecological improvements of the restored river sections and showed the achievements. Guidelines to assess the biological and hydro-morphological status of rivers were developed and there are plans to introduce them as Beijing Standards. Planning and implementation of measures, based on experiences in Central Europe, will be documented in a handbook. Keywords: River restoration–rehabilitation, Natural-modified rivers, European Water Framework Directive, Reference status, Biological and hydro-morphological assessment methods, Planning–implementation process